Nitrocellulose Membrane-Based Enzyme-Linked Immunoassay for Dengue Serotype-1 IgM Detection - León Sandoval, Segundo (1999)
OBJETIVES: To evaluate the sensitivity and specifity of a nitrocellulose membrane-based immunoassay for dengue IgM, with respect to capture enzyme immunoassay, for the diagnosis of dengue virus infection. METHODS: 101 serum samples were processed and divided into 2 groups: 53 from dengue serotype 1 (DEN1) infected patients, and 48 from healthy subjects. Both groups were tested with a nitrocellulose membrane-based IgM capture enzyme immunoassay (NMB-EIA) and also with an ELISA as referential pattern. RESULTS: NMB-EIA testing detected IgM anti-DEN1 in 94,34% of samples from infected patients, and in 14,58% of control samples, whereas ELISA fails to report false positive or false negative results. CONCLUSION: NMB-EIA appears to be a good alternative for dengue infection diagnosis.